CONTEXTUAL APPROACH TO TEACHING THE ELECTIVE DISCIPLINE “THEORY OF MASS COM- MUNICATION” TO BACHELORS OF PEDAGOGICAL UNIVERSITIES (SPECIALITIES “GEOGRAPHY” AND “MUSICAL ART”) - Duboviy, Zakhar; Lakomova, Olena (Visnyk universytetu imeni Alʹfreda Nobeli͡a︡. Serii͡a︡: Pedahohika i psikholohii͡a, 2024)
The article covers the main principles of the contextual approach in studying the elective course “Theory of Mass Communication” in pedagogical universities. The aim of the article is to substantiate the effectiveness of applying the contextual approach to teaching the elective course “Theory of Mass Communication” to undergraduate students in pedagogical universities (specialties “Geography” and “Music Art”); to develop situational tasks aimed at fostering media literacy, the ability to codify, and the creation of informational sectoral blocks for dissemination in educational and media spaces. In the research, methods of content analysis, specification, problem-posing, as well as task-based and contextual approaches were used. It has been found that the study of university-wide elective courses appeals to interdisciplinarity in thematic correlation. On the one hand, it involves developing a system of situational tasks that contribute to improving the professional training of students in the specialties “Geography” and “Music Art”. It has been substantiated that the contextual approach is oriented towards teaching material based on methodological foundations, theoretical sectoral knowledge, and forms of activity. The context in the study of academic disciplines involves transforming didactic material, where the objective meanings and significance of sectoral knowledge are transformed into the personal experience of the future teacher. The integral platform allows for the design of situational tasks, the resolution of which combines educational and educational-professional experience. Situational tasks, based on the contextual approach to teaching the course “Theory of Mass Communication”, are built considering the professional training of students in higher pedagogical institutions in the specified specialties (“Geography” and “Music Art”). The didactically processed field of mass communication as a university-wide discipline encompasses thematic blocks such as “Basics of Mass Communication”, “Artistic and Aesthetic Parameters of Mass Com- munication”, “Sociological and Psychological Dimensions of Mass Communication”, and “Mass Communi- cation in the Conditions of Digital Society”. A diachronic consideration of the development of mass communications allows for identifying the cul- tural and historical factors that shape the transmission paths of channels aimed at the recipients of certain knowledge. Addressing the diachronic consideration of mass media information significantly expands the un- derstanding of its essence and the processes of information transmission within mass communication models. It has been outlined that the social and psychological aspects of mass communication determine the language behaviour of professional communicators. This specific feature was taken as the basis in develop- ing situational tasks for communicators – future geographers and musicians. The prepared tasks were cor- related with the normative disciplines studied at the stage of professional training. It has been concluded that studying the elective course “Theory of Mass Communication” based on the contextual approach contributes to the development of professional competencies of teachers who transmit sec- toral information in the conditions of the informational educational environment. It has been proved that the study of semiotics of mass communication should be considered at the level of modelling cultural codes (since geographical names, musical and artistic works contain cultural and historical information, which is actualized in educational discourse at the stage of transmitting sectoral knowledge). Situational tasks, aimed at transmitting sectoral information at the level of a professional communicator (manifestation of language culture), should ap- peal to conducting press conferences as a type of communication, building one’s professional image. The expe- rience of students working with advertising material considering the professional training direction is positive.